2018
DOI: 10.1140/epjd/e2018-90150-7
|View full text |Cite
|
Sign up to set email alerts
|

Helium nanodroplets doped with copper and water

Abstract: Copper nanoparticles are promising, low-cost candidates for the catalytic splitting of water and production of hydrogen gas. The present gas-phase study, based on the synthesis of copper-water complexes in ultracold helium nanodroplets followed by electron ionization, attempts to find evidence for dissociative water adsorption and H2 formation. Mass spectra show that H2O-Cu complexes containing dozens of copper and water molecules can be formed in the helium droplets. However, ions that would signal the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…Krypton has 6 naturally occurring isotopes, including 4 with abundances above 10% ( 82 Kr at 11.58%, 83 Kr at 11.49%, 84 Kr at 57.00%, and 86 Kr at 17.30%); its average mass is 83.8 u. Hence, the spectrum of Kr-doped HNDs in Figure 1d (note the linear y-scale) is congested even though it covers only a small cluster size range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Krypton has 6 naturally occurring isotopes, including 4 with abundances above 10% ( 82 Kr at 11.58%, 83 Kr at 11.49%, 84 Kr at 57.00%, and 86 Kr at 17.30%); its average mass is 83.8 u. Hence, the spectrum of Kr-doped HNDs in Figure 1d (note the linear y-scale) is congested even though it covers only a small cluster size range.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported mass spectra of He n Cu + clusters, formed by doping neutral HNDs with copper and performing a subsequent electron ionization . For this system, the relative size is 0.77, slightly larger than that of Ne n Cu + .…”
Section: Discussionmentioning
confidence: 96%
“…32 With the exception of this work, there are only two other published mass spectrometric studies of singly charged noble metal ions complexed with more than two noble gas atoms: One from our lab which suggest that He6Cu + , He12Cu + , and He24Cu + , are particularly stable. 33 And another one by Froudakis et al who observed NenCu + (n  24) and ArnCu + (n  150). 34 The abundance distributions indicated enhanced cluster ion stability at n = 4 and 12 for NenCu + but at n = 4 and 6 for ArnCu + .…”
Section: Introductionmentioning
confidence: 94%
“…The paper by Raggl et al [31] reported the results of a gas-phase study of electron ionization of copperwater complexes formed in ultracold helium nanodroplets. This study was motivated by a potential use of copper nanoparticles as low-cost candidates for the catalytic splitting of water and production of hydrogen gas.…”
Section: Structure and Dynamics Of Atomic Cluster Systemsmentioning
confidence: 99%